Baicalin alleviates hyperglycemia-induced endothelial impairment via Nrf2. Issue 1 (January 2019) - Chen, Gen; Chen, Xiangjuan; Niu, Chao; Huang, Xiaozhong; An, Ning; Sun, Jia; Huang, Shuai; Ye, Weijian; Li, Santie; Shen, Yingjie; Liang, Jiaojiao; Cong, Weitao; et al.
Abstract : Baicalin is the major component found in Scutellaria baicalensis root, a widely used herb in traditional Chinese medicine, which exhibits strong anti-inflammatory, anti-viral and anti-tumor activities. The present work was devoted to elucidate the molecular and cellular mechanisms underlying the protective effects of Baicalin against diabetes-induced oxidative damage, inﬂammation and endothelial dysfunction. Diabetic mice, induced by streptozotocin (STZ), were treated with intraperitoneal Baicalin injections. Human umbilical vein endothelial cells (HUVECs) were cultured either in normal glucose (NG, 5.5 mM) or high glucose (HG, 33 mM) medium in the presence or absence of Baicalin for 72 h. We observed an obvious inhibition of hyperglycemia-triggered oxidative damage and inﬂammation in HUVECs and diabetic aortal vasculature by Baicalin, along with restoration of hyperglycemia-impaired nuclear factor (erythroid-derived 2)-like 2 (Nrf2) pathway activity. However, the protective effects of Baicalin almost completely abolished in HUVECs transduced with shRNA against Nrf2, but not with nonsense shRNA. Mechanistic studies demonstrated that HG decreased Akt and GSK3B phosphorylation, restrained nuclear export of Fyn and nuclear localization of Nrf2, blunted Nrf2 downstream target genes and subsequently induced oxidative stress in HUVECs. However, those destructive cascades were well prevented by Baicalin in HUVECs. Furthermore, LY294002 and ML385 (inhibitor of PI3K and Nrf2) attenuated Baicalin-mediated Nrf2 activation and the ability of facilitates angiogenesis in vivo and ex vivo. Taken together, the endothelial protective effect of Baicalin under hyperglycemia condition could be partly attributed to its role in downregulating reactive oxygen species (ROS) and inﬂammation via the Akt/GSK3B/Fyn-mediated Nrf2 activation.